2004
DOI: 10.1093/annonc/mdh359
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of ISIS 3521, an antisense oligodeoxynucleotide to protein kinase C alpha, in patients with previously treated low-grade non-Hodgkin's lymphoma

Abstract: ISIS 3521 has demonstrated anti-tumour activity in patients with relapsed low-grade NHL. There may be a potential role for this agent in combination with conventional chemotherapy for advanced low-grade lymphoma, and further trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Midostaurin (34) was the first PKC inhibitor evaluated in clinical trials; however, it has failed to demonstrate significant activity in clinical trials to date (35). ISIS 3521, a phosphorothioate antisense oligonucleotide targeting the 3 0 -untranslated region of PKC-a mRNA (36,37), demonstrated anticancer activity in various types of cancers, including tumors refractory to conventional chemotherapy (38,39), but has so far failed to exert clinically significant efficacy when combined with chemotherapy against advanced lung cancer in phase III trials (40). In contrast to these disappointing results, PKC-b inhibitor enzastaurin as a single agent showed promising results in phase II trials against diffuse large B-cell lymphoma (41), although one phase III trial in patients with recurrent glioblastoma found no superior effect to conventional therapy (42).…”
Section: Discussionmentioning
confidence: 99%
“…Midostaurin (34) was the first PKC inhibitor evaluated in clinical trials; however, it has failed to demonstrate significant activity in clinical trials to date (35). ISIS 3521, a phosphorothioate antisense oligonucleotide targeting the 3 0 -untranslated region of PKC-a mRNA (36,37), demonstrated anticancer activity in various types of cancers, including tumors refractory to conventional chemotherapy (38,39), but has so far failed to exert clinically significant efficacy when combined with chemotherapy against advanced lung cancer in phase III trials (40). In contrast to these disappointing results, PKC-b inhibitor enzastaurin as a single agent showed promising results in phase II trials against diffuse large B-cell lymphoma (41), although one phase III trial in patients with recurrent glioblastoma found no superior effect to conventional therapy (42).…”
Section: Discussionmentioning
confidence: 99%
“…They form duplexes with the target mRNA, thereby interfering with gene expression and production of target proteins. There have been a growing number of antisense oligonucleotides in clinical development as anti-cancer agents [1][2][3][4]. Various analytical methods, such as gel capillary electrophoresis (GCP) [1], high-performance liquid chromatograph (HPLC) [5] and HPLC-mass spectrometry (LC/MS) [6], have been developed and used in quantitating antisense oligonucleotides in patient samples from clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Trial discontinued due to severe myalgia in more than 50% of patients [119] ATM (aurothiomalate) Phase I trial in NSCLC, ovarian cancer and pancreatic cancer n = 15 Good tolerance [120] Translation inhibitors ISIS 3521 Phase I trial in advanced cancer (21-day infusion) n = 21 3 PR (ovarian cancer) 2 CR (lymphoma) 1 SD (NSCLC) [121] Phase I trial in advanced cancer (24-hour infusion) Not well tolerated [122] Phase II trial in low-grade non-Hodgkin's lymphoma n = 26 3 PR 10 SD [123] Phase II trial in colorectal cancer n = 16 No clinical activity [124,125] Phase II trial in high-grade astrocytomas n = 21 No clinical activity [124,125] Phase II trial in ovarian cancer n = 36 0 CR/PR 1 CA125 response [126] Phase I/II trial in combination with carboplatin and paclitaxel in NSCLC n = 53 Response rate 48% [127] Phase III trial in combination with gemcitabine in NSCLC n = 670 No clinical activity [128] Atu027…”
Section: Midostaurinmentioning
confidence: 99%
“…A further phase I study of weekly 24 h infusion was also tested but this was not as well tolerated as the 21-day infusion [122]. In phase II studies of ISIS 3521 monotherapy there were 3 partial responses in NHL [123], one CA125 response in refractory ovarian cancer [126], but no activity in other tumour types [124,125]. Phase I and II studies of ISIS 3521 in combination with carboplatin and paclitaxel in patients with NSCLC (n = 53) looked extremely promising with an objective response rate of 48% [127].…”
Section: Translation Inhibitorsmentioning
confidence: 99%